Addressing SIM Card and IMEI Security Vulnerabilities in Preventing Illegal Online Activities by Using Elliptic Curve Cryptography - Setyowati, Danny; Rimbawa, Danang (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The telecommunication system in Indonesia faces serious challenges due to the misuse of SIM card data and devices with illegal IMEIs, as seen in the case of mass registration of prepaid cards using fake or stolen identities in 2018. This problem is further exacerbated by the circulation of black market (BM) phones that use unregistered IMEI to avoid network blocking. As a result, these security loopholes are used to support illegal activities such as account registration on online gambling platforms. This study proposes the application of Elliptic Curve Cryptography (ECC) as a solution to improve SIM card data security and IMEI validation. ECC provides efficient and secure encryption methods to protect data, verify device authentication, and block illegal activities through telecommunication systems. The main contribution of this research is the development of ECC-based systems that can prevent the misuse of SIM card and device data, support the validation of legitimate devices, and tighten control over network access. The evaluation shows that ECC technology can be applied effectively in improving telecommunication security in Indonesia.